A grid of indicators as a tool for decision support and good management of urban planning instruments - Samir, Allouache; Bouchareb, Abdelouahab (Technium Social Sciences Journal, 2023)
Urbanization and the economic, social and environmental development of the city in Algeria are based on urban planning instruments. These instruments, once approved by the different deconcentrated directions of the state as well as the associations, become opposable to third parties and move directly to their implementation on the ground. To ensure the habitability of urban spaces, these urban planning instruments, whether approved, in the process of being approved or not yet launched, must have the characteristics of efficiency and profitability. The question that arises is how to ensure this efficiency and profitability of the instrument? In order for these instruments to meet these characteristics and be equal to the urban changes and needs of tomorrow, the use of good management of the instrument is essential, but this management can only be ensured through the establishment of a grid of indicators that will serve as a tool for monitoring and evaluating the degree of effectiveness and profitability of the instrument at the time of its execution. In the event that the instrument does not meet a given need, a decision will be taken to ensure its proper management, effectiveness and profitability.